Microwave sintering of cordierite precursor green bodies prepared by starch consolidation - Sandoval, María Laura (2011)
This paper reports on a study of the microwave sintering behavior of green disks prepared by the starch consolidation forming method to produce cordierite-based porous materials. Green disks were formed by thermogelling the aqueous suspensions of talc, kaolin and alumina (29.6 vol.%) and potato starch (11.5 vol.%) at 75 and 85 ºC for 4 h, drying and calcining. They were characterized by bulk density and apparent porosity measurements, and SEM. Microwave sintering was carried out at 1300 and 1330 ºC for 15, 20 and 25 min, applying 50 ºC/min. For purposes of comparison, an analysis of green disks prepared and calcined in the same conditions and conventionally sintered (1330 ºC for 4 h) was also made. The materials were characterized by XRD, bulk density and apparent porosity measurements, and microstructurally analyzed SEM. The results were analyzed considering the behavior of starch in aqueous suspension at varying temperatures, and the experimental conditions of consolidation and sintering.